Estimating Survival in Melanoma Patients With Brain Metastases: An Update of the Graded Prognostic Assessment for Melanoma Using Molecular Markers (Melanoma-molGPA) - Sperduto, Paul W. (Int J Radiat Oncol Biol Phys, 2017)
PURPOSE: To update the Diagnosis-Specific Graded Prognostic Assessment (DS-GPA) for a markedly heterogeneous patient population, patients with melanoma and brain metastases, using a larger, more current cohort, including molecular markers. METHODS: The original Melanoma-GPA is based on data from 483 patients whose conditions were diagnosed between 1985 and 2005. This is a multi-institutional retrospective database analysis of 823 melanoma patients with newly diagnosed brain metastases from January 1, 2006, to December 31, 2015. Multivariable analyses identified significant prognostic factors, which were weighted and included in the updated index (Melanoma-molG-PA). Multiple Cox regression was used to select and weight prognostic factors in proportion to their hazard ratios to design the updated Melanoma-molGPA in which scores of 4.0 and 0.0 are associated with the best and worst prognoses, as with all of the diagnosis-specific GPA indices. Log-rank tests were used to compare adjacent classes. RESULTS: There were 5 significant prognostic factors for survival (age, Karnofsky performance status [KPS], extracranial metastases [ECM], number of brain metastases, and BRAF status), whereas only KPS and the number of brain metastases were significant in the original Melanoma-GPA. Median survival improved from 6.7 to 9.8 months between the 2 treatment eras, and the median survival times for patients with Melanoma-molGPA of 0 to 1.0, 1.5 to 2.0, 2.5 to 3.0, and 3.5 to 4.0 were 4.9, 8.3, 15.8, and 34.1 months (P<.000l between each adjacent group). CONCLUSIONS: Survival and our ability to estimate survival in melanoma patients with brain metastases has improved significantly. The updated Melanoma-molGPA, a user-friendly tool to estimate survival, will facilitate clinical decision making regarding whether and which treatment is appropriate and will also be useful for stratification of future clinical trials. To further simplify use, a free online/smart phone app is available at brainmetgpa.com.